INTEGRATING THE QUR'ANIC PERSPECTIVE ON RELIGIOUS FREEDOM IN ISLAMIC EDUCATION: A STUDY OF NAHDLATUL ULAMA DA'WAH PRACTICES IN SALATIGA - Safrodin Safrodin; Ema Hidayanti; Widayat Mintarsih; Komarudin Komarudin (Nurul Jadid University, 2026)
This study examines how the Qur'anic principle of religious freedom is integrated into Islamic education and the da'wah practices of the Nahdlatul Ulama community in Salatiga. This research departs from the still-limited studies linking the value of religious freedom in the Qur'an with the practice of community-based Islamic education and da'wah. Using a qualitative case study design, data were collected through thematic analysis of Qur'anic interpretations and semi-structured interviews with religious leaders and Islamic education practitioners. The results show three main patterns. First, the principle of lā ikrāh fī al-dīn is internalized in da'wah through persuasive, dialogical, humanistic, and ethical communication without coercion. Second, this value is pedagogically transformed in inclusive and participatory learning to foster tolerance and respect for socio-religious diversity. Third, religious freedom is socially constructed through processes of externalization, objectivation, and internalization until it becomes a shared cultural norm. This study contributes to broadening the study of multicultural Islamic education by demonstrating that religious freedom is not only a normative concept but also a lived social and pedagogical process in Muslim communities.